The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3329/bjms.v17i2.35884
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Communication skills of nurses worked at the Hospitals Affiliated to Jahrom University of Medical Sciences, Iran

Abstract: Objective: Communicating with patients is not only among the principles of care, but it is considered as one of the key roles of nurses. As nurses are skilled in other clinical skills, their communication skills should also be adequate. The aim of this study is to determine nurses’ communication skills.Materials and Methods: This descriptive study was conducted in 2015 in hospitals affiliated to Jahrom University of Medical Sciences. 215 nurses participated in the study using census method. Data was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…36 Effective communication is transmission and receipt of the explicit message consciously and unconsciously created by a person and transferred to a receiver through verbal and nonverbal channel. 37 To transmit something competently, first of all one has to introduce-self and explain clearly the purpose of communication;then question appropriately, listen uninterruptedly, facilitate by providing summary of what has told before closing and then closethe communication with a pleasant thanks.…”
Section: Discussionmentioning
confidence: 99%
“…36 Effective communication is transmission and receipt of the explicit message consciously and unconsciously created by a person and transferred to a receiver through verbal and nonverbal channel. 37 To transmit something competently, first of all one has to introduce-self and explain clearly the purpose of communication;then question appropriately, listen uninterruptedly, facilitate by providing summary of what has told before closing and then closethe communication with a pleasant thanks.…”
Section: Discussionmentioning
confidence: 99%
“…They conclude that higher level in educational degrees results in better job positions and increased income and stable working conditions and consequent improved organizational citizenship behavior.Some studies [30][31][32][33][34][35] showed that job satisfaction, organizational commitment and organizational justice have some relationship with organizational citizenship behavior. If healthcare employees have a positive perception of their organizations, an effective context can be created for occurring enhanced citizenship behaviors with their maximum potentialities for improving performances and increasing the work quality 36 .On the other hand, A warm behavior with empathy can give the patients energy and decrease concerns about a patient's tolerance, anxiety, pain and suffering 37 . Taghinezhad and colleagues 20 considered some factors such as individual's personality, organizational culture, and staff's trust in managers as factors empowering employees to improve their organizational citizenship behavior.Akturan and HülyaGündüz 22 found a positive effectof knowledge sharing and organizational citizenship behaviors on creative behaviors in Turkish educational institutions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it found in another study that more than half of the nurses were had effective communication skills. Year of working experience, workload, and poor evidencebased utilization were the main contributing factors of the communication skills [14] . Also, it depicted that there was a moderate positive correlation between communicative competence and care behaviors of nurses (r = 0.5, P < 0.01) [15] .…”
Section: Overall Nursing Communication Skills In Preoperative Carementioning
confidence: 99%